Risk factors for pelvic organ prolapse in postpartum women: a retrospective cross-sectional study in Southwest China - Wan, Dehua; Qin, Taizhou; Guo, Ling; Zhang, Xueping; Wang, Huarong; Zheng, Zhongyan; Gan, Xiaoqin; Liu, Tianjiao; Lin, Yonghong (Frontiers in Medicine, 2025)
BackgroundPelvic organ prolapse (POP) is prevalent among postpartum women and can have detrimental effects on their urinary, sexual, and mental well-being. With recent shifts in birth policy and increasing parity in China, the risk of POP among postpartum women is rising. However, large-scale studies focusing on perinatal predictors of POP in Chinese population remain limited.MethodsWe conducted a retrospective study of 8,565 postpartum women who delivered at Chengdu Women’s and Children’s Central Hospital between January 2019 and April 2025. Demographic and perinatal characteristics were collected and pelvic floor function was assessed at sixth week postpartum. POP was diagnosed based on result of the POP-Q system, physical and ultrasound examination, and clinical assessment. Multinomial logistic regression analyses were performed to identify risk factors associated with POP.ResultsThe overall prevalence of POP was 72.83%, with most cases classified as Stage I. Occupational type, vaginal delivery, higher parity, and advancing maternal age were significantly associated with the occurrence of POP. Compared with white-collar workers, housewives had a reduced risk of POP (OR = 0.89, 95% CI: 0.81–0.98), whereas blue-collar workers showed no significant difference. Cesarean section was protective (OR = 0.14, 95% CI: 0.12–0.16, p < 0.001). High pregestational BMI was associated with a higher risk of POP, while gestational weight gain showed no significant association. Neonatal birth weight did not correlate with POP.ConclusionVaginal delivery, multiparity, advanced maternal age, and high pregestational BMI are risk factors for POP. Perinatal risk assessment and the potential value of preventive strategies, including weight management and individualized delivery planning are essential for mitigating the risks of postpartum POP.